Marketing mix factors that influence to decision buying’s cultural products of tourist in Nakhonpathom province - Ichayanan, Kiatisuk (Journal of Management Science Nakhon Pathom Rajabhat University, 2018)
The research on Marketing mix factors that influence to decision buying’s cultural products of tourist in Nakhonpathom province aimed to : 1) study tourist behavior to buy cultural product; 2) study marketing mix factors that influence to make decision to buy cultural product. 400 samples were collected from tourists who buy cultural product in Nakhonpathom province. analytical data with mean, percentage and standard deviation. Used First and second order Confirmatory Factor Analysis to test the hypothesis by using LISREL, program. The research revealed that 1) Tourist behavior study was found that most frequency of buying was less than one time per month, first memorized souvenir in NakhonPathom province was Kao-Lam, family had influence to buy, favorite place to buy was phrapathom jedi and average buying expenditures were 132 baht per time. 2) Buying decision was influenced by marketing mixes (4P’s) significantly. The top three influence factors are price promotion and place that factor loading were 0.85, 0.69, and 0.49 respectively. The power of forecast: R square (R2) were 92, 83 and 70 respectively. Article history : Accepted 22 June 2014 SIMILARITY INDEX = 0.00